Review of the textbook "History of law enforcement authorities of Ukraine" - Sviderska, Nataliia; Kura, Dmytro (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
Review of the textbook "History of law enforcement authorities of Ukraine"